Evaluation of Agricultural Credit Facility in Agricultural Production and Rural Development (Global Journal of Human-Social Science, 2014)
Lack of capital has been identified as one of the constraints faced by small scale farmers. The aim of this research work was to examine the effect of agricultural credit on agricultural production among small scale farmers with specific objectives to; (1) determine its effect on farm size and (2) evaluate the quantity of inputs and outputs among small scale farmers. Structured questionnaires were administered to 136 farmers, who had been selected using the stratified random sampling technique, and the data obtained were summarized into percentages. Regression analysis was adopted to assess the impacts of socio-economic factors on loan size among farmers, while Cobb-Douglas Production Function Analysis (CDPFA) was used to test the relationship between key independent variables such as loan amount, farm size, inputs and farm output as the dependent variable. The analysis revealed a significantly high (R2= 0.922) degree of relationship between the dependent variable and the independent variables; gender, age, education, family size, farm size, farming experience. The Adjusted coefficient (R2 = 0.918) revealed that 91.8 % variation in the size of loan explained by the changes in variables. The F-test significantly showed the joint effect of variables in the model on the size of loan. And on the hypothesis two, the independent variables; loan amount, farm size, and inputs explained the variation in the total value of output of the farmers. The study therefore shows that access to agricultural credit impacts positively on agricultural production. Government and the organized private sector should regularly and timely offer credit to farmers.
Keywords: agricultural production; farmers; cob-douglas; loan; rural development; small scale